2011
DOI: 10.3866/pku.whxb20110508
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on the Photophysicochemical Properties of Tetra(tert-butylphenoxy)phthalocyaninato Zinc(II)

Abstract: The solvent viscosity dependence of the photophysical and photochemical properties of tetra(tert-butylphenoxy)phthalocyaninato zinc(II) (ZnTBPPc) is presented. The fluorescence quantum yields (ΦF) and Stern-Volmer′ s constant (KSV) for ZnTBPPc fluorescence quenching by benzoquinone in all the solutions followed a semi-empirical law that depends only on the solvent viscosity. ΦF values vary between 0.08 in tetrahydrofuran (THF) and 0.14 in dimethylsulphoxide (DMSO). Triplet quantum yields (ΦT) and lifetimes (τT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…This E-type delayed fluorescence is attributed to enhanced intersystem crossing in presence of dissolved oxygen [ 34 ]. It also has been shown that triplet lifetime increases with the increase in solvent viscosity [ 37 ]. Gratz et al [ 38 ] have found that dwell time, which is a measure of efficiency for triplet-state accumulation, for indocyanine green sodium iodide (ICG-NaI), in N2-bubbled solutions of dye in DMSO is in the range of 35 ns while this value for solutions of this dye in N2-bubbled water is only 1.2 ns.…”
Section: Resultsmentioning
confidence: 99%
“…This E-type delayed fluorescence is attributed to enhanced intersystem crossing in presence of dissolved oxygen [ 34 ]. It also has been shown that triplet lifetime increases with the increase in solvent viscosity [ 37 ]. Gratz et al [ 38 ] have found that dwell time, which is a measure of efficiency for triplet-state accumulation, for indocyanine green sodium iodide (ICG-NaI), in N2-bubbled solutions of dye in DMSO is in the range of 35 ns while this value for solutions of this dye in N2-bubbled water is only 1.2 ns.…”
Section: Resultsmentioning
confidence: 99%